Assessment of health care cost for complex surgical patients: review of cost, re-imbursement and revenue involved in pancreatic surgery at a high-volume academic medical centre. Issue 4 (April 2015) - Kachare, Swapnil D.; Liner, Kendall R.; Vohra, Nasreen A.; Zervos, Emmanuel E.; Hickey, Todd; Fitzgerald, Timothy L.
Abstract: Background: Pancreatic surgery is complex with the potential for costly hospitalization. Methods: A retrospective review of patients undergoing a pancreatic resection was performed. Results: The median age of the study population was 64 years. Half of the cohort was female (51%), and the majority were white (62%). Most patients underwent a pancreaticoduodenectomy (PD) (69%). The pre-operative age-adjusted Charlson comorbidity index was zero for 36% ( n = 50), 1 for 31% ( n = 43) and ≥2 for 33% ( n = 45). The Clavien–Dindo grading system for post-operative complication was grade I in 17% ( n = 24), whereas 45% ( n = 62) were higher grades. The medians direct fixed, direct variable, fixed indirect and total costs were $2476, $15 397, $13 207 and $31 631, respectively. There was a positive contribution margin of $7108, whereas the net margin was a loss of $6790. On univariate analyses, age, type of operation and complication grade were associated with total cost ( P ≤ 0.05), whereas operation type and complication grade were associated with a net margin ( P = 0.01). These findings remained significant on multivariate analysis ( P < 0.05). Conclusions: Increased cost, reimbursement and revenue were associated with type of operation and post-operative complications.